ANALYTICAL STUDY THE METHOD OF DAKWA IN AN-NAHL 125-128 IN THE TESTAMENT OF MA’ALIM AL-TANZIL BY IMAM AlL-BAGHAWY - Muhammad Akbar Mawaldi; Andri Nirwana AN; Nazar Fadli (Profetika: Jurnal Studi Islam, 2024)
Da'wah is in principle an effort by someone to convey the teachings of Islam to others, both those who already believe in the truth of Islam, and those who do not have faith in the truth of Islam, both to individuals and groups. The purpose of this study is to find out how the tafsir Ma'alim Al-Tanzil analyzes Qs An-nahl verses 125-128 in the frame of the da'wah method and also to find out how the concept of the da'wah method in Qs An-nahl 125-128. This research is a literature study research. The sources of data used are primary and secondary data from the Qur'an and the book of tafsir Ma'alimu An-Tanzil by Imam Al-Baghawy, as well as previous data collected and reported by people outside the researcher and obtained from libraries, journals, articles and books related to the problem studied. The data will then be analyzed using the Tahlily method. The conclusion of the analytical study of the da'wah method in QS An-nahl verses 125-128 in the tafsir ma'alim al-manzil by Imam Al-Baghawy explains how to preach using the wisdom method based on the Qur'an wisely, then with the matzoh Hashanah method in the form of good advice, and with the method of yujadilu bill hiya ahsan, which is to argue in a good way without persecute who are opposed to debate. Then it is explained how to reward the actions of others without exaggerating them.